The leadership integrity challenge : - Morler, Edward E. (Sanai Publishing, 2005)
The book offers the tools for how to develop a core competency of assessing and facilitating emotional maturity. An organization whose memebers have this ability significantly expands its potential for creating a culture of character and integrity.